Basic methods of assortment portfilio analysis of the group - Krainiuchenko (Fornolyak), Olga; Chaika, Ivanna (My University, 2014)
Article considers basic methodological approaches to the study of assortment portfolio of the company; outlines their advantages, disadvantages and features of the application; proposes the possibility and necessity of integrated usage of proposed methods.
Keywords: асортиментний портфель; ABC-аналіз; метод Дібба-Сімкіна; рейтинговий аналіз; assortment portfolio; BCG matrix; ABC analysis; rating analysis; кафедра маркетингу